The CCL Guide to Leadership in Action: How Managers and Organizations Can Improve the Practice of LeadershipThe CCL Guide to Leadership in Action: How Managers and Organizations Can Improve the Practice of Leadership, edited by Wilcox Martin and Rush Stephen. San Francisco: Wiley, 2004. - Glinow, Mary Ann Von (Academy of Management Review, 2005)
The article reviews the book ?The CCL Guide to Leadership in Action: How Managers and Organizations Can Improve the Practice of Leadership,? edited by Martin Wilcox and Stephen Rush.